Cricket related hand injury is associated with increased odds of hand pain and osteoarthritis - Shah, K; Furniss, D; Collins, GS; Peirce, N; Arden, NK; Filbay, SR (Springer Nature, 2020)
Radiographic osteoarthritis (OA) is most prevalent in the hand. The association of hand injury with pain or OA is unclear. The objective was to describe the relationship between hand injury and ipsilateral pain and OA in cricketers. Data from former and current cricketers aged ≥ 30 years was used. Data included history of cricket-related hand/finger injury leading to > 4 weeks of reduced exercise, hand/finger joint pain on most days of the last month, self-reported history of physician-diagnosed hand/finger OA. Logistic regression assessed the relationship between injury with hand pain (in former cricketers) and with OA (in all cricketers), adjusted for age, seasons played, playing standard. Of 1893 participants (844 former cricketers), 16.9% reported hand pain, 4.3% reported OA. A history of hand injury increased the odds of hand pain (OR (95% CI) 2.2, 1.4 to 3.6). A history of hand injury also had increased odds of hand OA (3.1, 2.1 to 4.7). Cricket-related hand injury was related to an increased odds of hand pain and OA. This highlights the importance of hand injury prevention strategies within cricket. The high prevalence of hand pain is concerning, and further research is needed to determine the impacts of hand pain.